EFEKTIVITAS OPAC SEBAGAI SARANA TEMU KEMBALI INFORMASI DI UPT PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH MAGELANG (UNIMMA) - Rizki Shofak Isnaini; Jamzanah Wahyu Widayati (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
Evaluation of information retrieval tool is very important to find out how far the retrieval system has worked. This study evaluates the OPAC of Muhammadiyah University of Magelang (UNIMMA) by determining the effectiveness of the information retrieval system seen from the relevance of the data displayed with the data requested by the user. This is descriptive quantitative research that calculates the value of recall and precision, while the data collection is conducted through literature studies and documentation. Based on the data collected, it can be concluded that OPAC UNIMMA is in the effective category with a high level of precision, and in the value range of 0.68 - 1.00 with recall and precision values respectively 0.77 or 77% and 0.84 or 84%. However, from the observations on each class number, it is found that the class number has a higher recall value than the precision, ie: the class numbers of 200, 800, and 900.